The Correlation of Shoe Size and Component Size of Primary Total Knee Arthroplasty - van Egmond, Jeroen Cornelis; Verburg, Hennie; Hesseling, Brechtje; Mathijssen, Nina Maria Cornelia (The Journal of Knee Surgery, 2020)
Preoperative planning is an important phase of total joint arthroplasty. Current template programs and methods only provide moderate accuracy for implant size prediction. Recently, a relationship between shoe size and implant size was found. We hypothesized that shoe size shows a high percentage of agreement for implant size of both femoral and tibial component size in primary total knee arthroplasty (TKA). The aim of this study was to investigate the correlation and agreement between shoe size and TKA implant size. We performed a retrospective cohort study. Of all patients, who underwent primary TKA between September 2013 and March 2016, shoe size and knee implant sizes were collected. Cross-tabulation was used to determine the correlation and agreement between shoe size and implant size. A total of 489 patients (498 TKA) were included. The correlation coefficient for femoral and tibial component with shoe size was 0.751 and 0.759, respectively. When a deviation of ± 1 component size was allowed, shoe size gave at least 94% agreement score for femoral component and at least 86% agreement score in tibial component. We conclude that both femoral and tibial component size have a good correlation with shoe size. Therefore, shoe size may be used as a valuable predictor in preoperative implant size planning for primary TKA. The level of evidence for this study was Level IV.
Keywords: total knee arthroplasty; preoperative planning; shoe size; template